Mainshock-Integrated Aftershock Vulnerability Assessment of Bridge Structures - Xuan Guo (Applied Sciences, 2020)
Seismic fragility analysis is often conducted to quantify the vulnerability of civil structures under earthquake excitation. In recent years, besides mainshocks, strong aftershocks have been often witnessed to induce structural damage to engineered structures, including bridges. How to accurately and straightforwardly quantify the vulnerability of bridges due to sequential mainshocks and aftershocks is essential for an efficient assessment of bridge performance. While recognizing the limitation of existing methods, this paper proposes a mainshock integrated aftershock fragility function model, which empirically encodes the effects of mainshocks and retains the simple form of traditional fragility curves. A pile foundation-supported bridge system is modeled considering seismic soil-structure interaction to demonstrate the proposed fragility model. Numerical examples show that the resulting fragility curves incorporate the initial value for the probability of collapse of the bridge system due to a mainshock and the effects of the variable aftershocks conditional on the mainshock. Statistical analysis confirms that the proposed model fits the simulated vulnerability data (e.g., seismic intensities of aftershocks and the response demands conditional a select mainshock ground motion) both accurately and robustly.